The association between family structure and physical activity among medical students - Ignatio Rika Haryono; Sabrina Clarissa Suwandi; Nawanto Agung Prastowo (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: Lack of physical activity has become a tremendous health problem in young people, notably in the digital communication era. Due to burdensome academic tasks, the situation may be more rigorous for medical students. The family structure is supposed to influence children's physical activity patterns. Aim of the study: This study aimed to investigate the effect of family structure on physical activity levels in medical students. Methods: This cross-sectional study was followed by 109 students; 75 (68.8%) were female. Gender, family structure, parents' level of physical activity, number of families, and the presence of grandparents were included as independent variables. In contrast, students' level of physical activity was a dependent variable. Data on independent variables were obtained through a guided interview. The International Physical Activity Questionnaire (IPAQ) was applied to assess students' level of physical activity. Variables were dichotomously categorized to simplify statistical testing. Chi-square was applied to reveal the relationship between the dependent and independent variables. A p-value of less than 0.05 was considered significant. Results: 39 (35.8%) students had low IPAQ score, 47 (43.1%) moderate, and 23 (21.1%) high. Most students (61.4%) lived in a nuclear family. There were 55 students (50.5%) who lived with family members less than 5; only 31 (28.4%) reported the presence of grandparents in their homes. Most students' parents reported doing sufficient regular exercise (73.1%). Students' IPAQ score was associated with the family type (OR 3.56, 95% CI 1.53-8.20, p = 0.002) and the presence of grandparents (OR 3.76, 95% CI 1.57-9.00, p = 0.002). Conclusion: Medical students who lived in a nuclear family and lived without their grandparents had higher physical activity levels.